The worldwide prevalence of intestinal helminthic parasites among food handlers: A systematic review and meta-analysis. (June 2023) - Eslahi, Aida Vafae; Olfatifar, Meysam; Zaki, Leila; Pirestani, Majid; Sotoodeh, Simin; Farahvash, Mohammad Aidin; Maleki, Aisa; Badri, Milad
Abstract: Food handlers have a major role in transmission of food-borne parasitic infections including intestinal helminths. The objective of the present study was to assess the global prevalence of intestinal helminthic parasites among food handlers. Multiple databases (PubMed, Scopus, ProQuest, Web of Science, Science Direct and Google Scholar) were searched for literature published from 1990 to 2022. Pooled prevalence was estimated using the meta-package in R (version 3.6.1). One hundred twenty seven articles, including 220, 705 individuals, were considered in this study. The global pooled prevalence (95% confidence interval) was 0.115% (0.091% - 0.141%). The highest pooled prevalence was reported from Africa (0.160%, 0.124%–0.210%). The most prevalent helminth was Ascaris lumbricoides (0.062%, 0.047%–0.079%). Moreover, among different countries, Ghana had the highest pooled prevalence (0.496%, 0–1.000%). This study revealed a high prevalence of intestinal helminths among food handlers. Routine parasitological investigation, food safety and personal sanitation training are recommended to prevent intestinal helminths transmitted by food handlers.